Design and Narrative Structure for the Virtual Human Scenarios - Göbel, Stefan; Iurgel, Ido Aharon; Rössler, Markus; Hülsken, Frank; Eckes, Christian (International Journal of Virtual Reality, 2007)
This article describes the design of the two application scenarios of the Virtual Human project and its integration into the Virtual Human system. This includes overall concepts and considerations of the demonstrators for the two application scenarios (learning, edutainment) as well as underlying methodic-didactic aspects for knowledge transmission and narrative concepts for story structure and story control during run-time of the system. Hence, in contrast to traditional learning systems with virtual characters as virtual instructors, an exciting and suspenseful interactive information space has been created. On the one hand, the methodic-didactic methods and VH learning model guarantee learning effects, on the other hand narrative structures and an emotion module provide the ground for a playful and exciting story environment, whereby the users can interact and discuss with a set of virtual characters.